Evaluation of the Implementation of WHO Infection Prevention and Control Core Components Among Health Care Facilities - Ameen, Blend Barzan; Haji, Ramand Mohammed; Babakr , Sharif Hama (Kurdistan Journal of Applied Research, 2024)
Programs for infection prevention and control comprise a range of action plans, including antiseptic regulations, a healthcare worker training program, and the monitoring of healthcare-associated infections. The purpose of the study is to evaluate the World Health Organization’s implementation of infection prevention and control programs level in Ranya tertiary and healthcare facilities. A cross-sectional study was conducted at Eight healthcare institutions in the Ranya administration in the Kurdistan Region of Iraq from February 2023 to the end of August 2023 using the World Health Organization Infection Prevention and Control Assessment Framework (IPCAF) checklist. The IPCAF consists of eight segments and each part has a score of 100, hence with the greatest score of 800. The respondents in this study were the heads of facilities and employees engaged in IPC-related tasks. The results show that 6 Healthcare staff (75%) had basic IPC levels, and they scored 235, 207.5, 222.5, 330, 362.5, and 347.5 out of 800 points respectively. Further, 2 Healthcare staff (25%) had inadequate IPC levels, and they scored 200 and 180 points. In addition, among the 8 IPC core components, the built environment and materials/equipment at the facility level (C8) had the highest scores, while minimum scores were observed in education, training (C3) and healthcare-associated infection surveillance (C4). In conclusion, the Ranya HCF facilities have certain working IPC aspects without appropriate implementation; further, practically all components need significant improvement.